PENGARUH SOCIAL MEDIA MARKETING TIKTOK TERHADAP BRAND EXPERIENCE - Suci Sari; Gugyh Susandy (STIESA Press, 2024)
The existence of social media is now no longer used as a means of entertainment, but also as a modern marketing tool that is able to reach buyers on a wider scale. TikTok is a digital entertainment platform that has expanded into digital marketing tools. The tight competition in the business world means that many companies need Big77 to be dynamic in implementing appropriate marketing strategies. This research aims to analyze the influence of social media marketing, namely TikTok, on brand experience. The sample is 70 respondents who have used Wardah Beauty products and are active on TikTok social media. The research results prove that social media marketing activities via TikTok can influence brand experience. However, the brand experience of Wardah Beauty Cosmetics cannot be grown from the results of social media marketing carried out via the TikTok platform. Brand loyalty is formed from the experience of the Wardah Beauty cosmetic brand which is rated quite highly in the eyes of consumers. The sample for this research consisted of 70 people. The sample technique used was purposive sampling. Purposive sampling is a technique for sampling data sources with certain considerations. Data analysis uses quantitative descriptive analysis, simple linear regression model, classical assumption test. Hypothesis testing uses partial tests and coefficient of determination tests (R2) and tests (t), while data processing uses SPSS 22 based on partial tests (t tests). The results of this research show that partially, social media marketing has a positive effect on brand experience in the Wardah Beauty TikTok survey. However, based on the R2 Determination Coefficient Test), the work of social media marketing variables has a small influence on brand experience. This is proven by the determination coefficient value of 44.1%